The policy instruments of European front-runners: Effective for saving energy in existing dwellings? - Murphy, Lorraine Colette (A+BE | Architecture and the Built Environment, 2016)
Existing dwellings receive frequent attention in climate change policy given the wealth of cost-effective, but un-exploited, energy saving potential within their walls. Policy attention also recognises the need for instruments that can navigate around barriers and maximise opportunities to achieve deep carbon reductions. However, there is a lack of evidence and knowledge about the instruments that can boast of success. In response to this knowledge gap, the instruments that form the main policy response to reduce energy consumed for space and water heating in existing dwellings in several front-runner European countries are assessed. Aims are to include, and to go beyond, an understanding of effectiveness based on reported reductions in CO2 emissions and/or monetary savings on energy bills. Effectiveness is also judged on the basis of how instruments reflect policy instrument and energy policy concepts drawn from literature. Results show that the instruments that define action of front-runners differ significantly. Front-runners fail to reconcile all the identified concepts in their main instruments but some feature strongly. In this regard, selected countries established their main instruments over two decades ago, reflecting the concept of long-term instrument development and support. However, few front-runners adequately monitor and evaluate instruments to illuminate cause and effect. Front-runners struggle to diversify their core instrument approaches to capture ‘hard to reach households’ such as the private rental sector and lower-income households. The divergence in the instruments that form the main policy response of front-runners allows for the characteristics of a range of instruments to be analysed including regulations, information tools, taxes and incentives.